Fluoxetine-induced sleep bruxism in an adolescent treated with buspirone: A case report - SABUNCUOĞLU, OSMAN TALAT (My University, 2009)
Sleep bruxism, the involuntary grinding and/or clenching of teeth during sleep, may occur in young children and may be secondary to medication use, especially selective serotonin reuptake inhibitors (SSRIs). The mesocortical disinhibition produced by SSRIs may lead to dopamine depletion that manifests itself as nocturnal bruxism, a specific form of akathisia. This may be prevented by using buspirone, a 5-HT1A agonist that reduces serotonergic activity and increases dopaminergic activity. This article reports on a case history of an adolescent with fluoxetine-induced bruxism that was successfully treated with buspirone. As SSRI use is on the rise for treating childhood psychiatric disorders, this case report highlights the importance of recognizing SSRI-induced bruxism and the possible related adverse dental side effects. Furthermore, this report supports the efficacy of a treatment strategy in adolescents, which has previously been reported only for adult patients. © 2009 Special Care Dentistry Association and Wiley Periodicals, Inc.
Keywords: Adolescent; Buspirone; Fluoxetine; Sleep bruxism